PERNIKAHAN DI BAWAH UMUR DAN KEUTUHAN KELUARGA : KASUS DI INDRAMAYU - Abdurrasyid Ridha (Tatar Pasundan: Jurnal Diklat Keagamaan, 2020)
Although there is a minimum age regulation of marriage, a case of underage marriage still exists The purpose of research is to know the implication of underage marriage to household integrity. This research type is field research and quantitative descriptive. The result shows that from 15 cases of underage marriage, 10 cases or 67 percent are still intact in marriage. While the remaining 5 cases ends in divorce. It implies that 33 percent of the total underage marriage in 2014 in Gabuswetan ended in divorce. To sum up, underage marriages have great implication to household integrity. They are very vulnerable to divorce.Keywords: underage marriages; divorces; children’s marriage